2022
DOI: 10.1128/spectrum.01896-21
|View full text |Cite
|
Sign up to set email alerts
|

Specific Strains of Honeybee Gut Lactobacillus Stimulate Host Immune System to Protect against Pathogenic Hafnia alvei

Abstract: Honeybees are essential pollinators supporting global agricultural economies and food supplies. Recent honeybee decline has been linked to several factors, while pathogen infection is considered one of the most significant contributing factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 62 publications
0
50
0
Order By: Relevance
“…Within this megadiverse insect order, a large number of species engage in different feeding habits and ecological habitats, yet there is still a lack of comprehensive investigation into the association with bacterial partners. The gut microbiota of insects, as well as other animals, provide the host with key functions in diet digestion [ 53 , 54 ], abiotic stress detoxification [ 55 ], nutrition supplementation [ 56 ], pathogen resistance [ 57 , 58 ], etc. In this work, insects of three heteropteran infraorders were selected for the characterization of their gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Within this megadiverse insect order, a large number of species engage in different feeding habits and ecological habitats, yet there is still a lack of comprehensive investigation into the association with bacterial partners. The gut microbiota of insects, as well as other animals, provide the host with key functions in diet digestion [ 53 , 54 ], abiotic stress detoxification [ 55 ], nutrition supplementation [ 56 ], pathogen resistance [ 57 , 58 ], etc. In this work, insects of three heteropteran infraorders were selected for the characterization of their gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lactiplantibacillus plantarum can disturb the natural symbiotic microbiota and significantly increase the mortality of Nosema ‐infected honeybees (Ptaszynska et al ., 2016). Several bacteria strains isolated from the honeybee gut have been demonstrated to be protective against pathogenic microorganisms (Carina Audisio et al ., 2011; Miller et al ., 2021; Lang et al ., 2022). More understanding of the microbial community of bumblebees is urgently needed to improve bumblebee health and to provide theoretical support for the conservation of commercial and wild bumblebees.…”
Section: Potential Roles Of the Gut Microbiota In Pathogen Resistancementioning
confidence: 99%
“…Studies have shown that honeybee gut microbiota affects host nutrition, weight gain, and endocrine signaling [20]. Moreover, gut microbial members also have immunomodulation effects on bees [21] and protect honeybees from the opportunistic pathogens [22], which is critical to their survival and health in a complex environment [23]. Furthermore, there are known interaction between honeybee intestinal microorganisms and some honeybee diseases, for example, Nosema ceranae infection can promote proliferation of yeasts in honeybee gut and cause disease [24].…”
Section: Introductionmentioning
confidence: 99%